2014
DOI: 10.1590/s1413-35552012005000132
|View full text |Cite
|
Sign up to set email alerts
|

Cold water immersion of the ankle decreases neuromuscular response of lower limb after inversion movement

Abstract: BackgroundCryotherapy has been associated with a significant decrease in nerve conduction velocity and muscle contraction with possible effects on exercise and physical training. ObjectivesTo quantify the electromyographic response of the lateral gastrocnemius, tibialis anterior, fibularis longus, rectus femoris and gluteus medius to ankle inversion following cold water immersion. MethodThe peak values of the root mean square (RMS) were obtained from 35 healthy and active university subjects after the use of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…Regarding acute cooling intervention applied before exercise, studies have reported decreased muscle activation (EMG amplitude) in response to the cold intervention [ 45 , 46 ]. Other investigators reported no significant changes [ 47 ] or increased muscle activation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding acute cooling intervention applied before exercise, studies have reported decreased muscle activation (EMG amplitude) in response to the cold intervention [ 45 , 46 ]. Other investigators reported no significant changes [ 47 ] or increased muscle activation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo demonstrou a redução da velocidade de condução nervosa e de contração muscular em atletas universitários do sexo masculino, após a imersão em água gelada, também até 5ºC, utilizando para isso a eletromiografia de superfície (EMG). No protocolo experimental utilizaram imersões entre 10, 20 ou 30 minutos de duração, e os resultados mais significativos ocorreram após 20 minutos, e ainda relataram que após o experimento, as alterações sensoriais perduraram por mais de 30 minutos, sendo tais mudanças ocorridas justificadas por alterações no controle neuromuscular [19]. No presente estudo, foi verificado que tais alterações no comportamento neuromuscular no caso dos hemiparéticos proporcionaram transferência de peso para o lado acometido de forma rápida e efetiva, proporcionando uma estratégia terapêutica de baixo custo e efetiva para promover os ajustes necessários ao controle postural durante o atendimento.…”
Section: Discussionunclassified
“…Reportando apenas pequena diminuição da inflamação muscular após um período de 72 horas. Por outro lado, no estudo realizado por Macedo et al 16 , identificou-se que após a aplicação da crioterapia de imersão em água fria, houve diminuição significativa na atividade eletromiográfica da musculatura do membro inferior, apresentando eficiência no decréscimo da resposta inflamatória no músculo esquelético.…”
Section: Discussionunclassified